(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The kidney damage caused by type 2 diabetes mellitus (T2DM) is more varied than that of type 1 diabetic mellitus (T1DM). People with type 2 diabetes don’t always get classical diabetic glomerulosclerosis, which is marked by a drop in the glomerular filtration rate (GFR), albuminuria, and retinopathy. If the estimated glomerular filtration rate (eGFR) is less than 60 mL/min per 1.73 m² of body surface area (BSA), then the person has chronic renal insufficiency.